2023
DOI: 10.3389/fmed.2023.1225689
|View full text |Cite
|
Sign up to set email alerts
|

Research is still limited on nutrition and quality of life among older adults

Mary Beth Arensberg,
Jaime Gahche,
Raquel Clapes
et al.

Abstract: IntroductionGlobally, the number of older adults is growing exponentially. Yet, while living longer, people are not necessarily healthier. Nutrition can positively impact healthy aging and quality of life (QoL). Two decades ago, nutrition and diet were rarely viewed as key QoL domains, were not part of QoL screening, and QoL studies frequently used unvalidated tools. It is unclear how the nutrition and QoL research area may have since evolved.MethodsA scoping review was conducted in Pubmed of research with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Nutrition interventions assist older individuals in meeting nutritional requirements, maintaining physical and cognitive function, key components of QoL. However, we identified few studies focusing on this population, consistent with Arensberg et al findings [ 183 ]. The absence or exclusion of older adults from clinical trials restricts data availability, forcing clinicians to make treatment decisions for older adults without adequate guidance [ 184 ].…”
Section: Discussionsupporting
confidence: 89%
“…Nutrition interventions assist older individuals in meeting nutritional requirements, maintaining physical and cognitive function, key components of QoL. However, we identified few studies focusing on this population, consistent with Arensberg et al findings [ 183 ]. The absence or exclusion of older adults from clinical trials restricts data availability, forcing clinicians to make treatment decisions for older adults without adequate guidance [ 184 ].…”
Section: Discussionsupporting
confidence: 89%
“…Further, we identified that a wide variety of instruments measuring different attributes had been used to describe QoL. This disparity can make it difficult for professionals unfamiliar with QoL measurements to choose a tool best aligned with their research purposes 11 . Such findings reiterate the observations of Siette et al that disagreement on core QoL concepts and the inability of a single tool to meet every need have contributed to the lack of development of a standard QoL measure 8 …”
Section: Discussionmentioning
confidence: 66%
“…The first step in our research was selection of common, validated QoL instruments used in community-living older adult populations. Our previous scoping review of QoL and nutrition research in older adults 11 found that Siette et al had published a systematic review in 2021, describing 29 QoL instruments that were (1) designed for adults (>18 years of age), (2) available in English, (3) used in peer-reviewed research examining QoL outcomes in adults >65 years of age from various care settings (home care, support center, residential care, assisted living group facilities, training facilities, and primary care), and (4) previously assessed for validity and/or reliability 8 . From the 29 QoL instruments described by Siette et al, 8 we selected 20 QoL instruments that were (1) used in countries with developed economies based on the United Nations definition of a “developed economy” 14 and (2) used in community care, that is, home care (supported independent living at home), a support center (provided care for older adults not fully independent, including care provided through senior and adult day centers), and/or primary care.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations